The Analysis of Zach’s Homosexual Identity in Shelter (2007) - Irmgard Papilaya; Surya Sili; Chris Asanti (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni dan Budaya, 2021)
Homosexual identity formation is the process when someone comes first to consider themselves become a homosexual. It means that homosexual identity formation is when someone considered he/she becomes a homosexual. There are six stages of homosexual identity formation from Vivienne Cass which are, identity confusion, identity comparison, identity tolerance, identity acceptance, identity pride, and identity synthesis. This theory explained that in order for someone to change from non homosexual to homosexual, they will experience these stages of identity formation. These four stages of homosexul identity formation can be found in Zach character in the Shelter film.  The purpose of this research was to find out the the character of Zach undergo the stages of homosexual identity formation in his transformation from a non homosexual person to homosexual in the Shelter film (2007). This research is conducted as a qualitative research. The data of this research were the dialogue, duration, action, word, and picture based on the film. This research has  two data sources which is the Shelter film (2007), and also the script of the film itself. The data in this research were then analyzed by using Vivienne C in order to get deeper understanding and the character , Abram’s theory of characterization is adopted. The result of this research proved and showed that in Shelter film (2007) Zach went the six stages of Homosexual Identity Formation in his process becoming a homosexual person.